A Development of A Learning Management System for E-Lecture (PIMC) - Ratree, Surasit; Petsangsri*, Sirirat (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The purposes of this research study were to develop a Learning Management System (LMS) for e-lecture created by PIMC (Presentational Instructor Media Creator) program, and to determine the functionalities and the level of quality of the system. Ten features of LMS were created as follow: 1) content editor, 2) database link, 3) registration, 4) import/export content, 5) communication tools, 6) file manager, 7) test manager, 8) custom interface design, 9) course tracker, and 10) print complier. The LMS was developed and modified from A Tutor, an open sourced system, into a new form of learning management system that was suitable to the need of particular Thai educators, and was capable of holding large steaming videos/lectures created from PIMC programs. Software packages used to develop the system were MySQL, Apache Web Server, PHP, Windows operating system, and EditPlus. When the LMS was completed, the experts inspected their function using software usability criteria. Eleven subjects were used to evaluate the functions of the system using 5 rating scale questionnaires. The research findings revealed that, 1) ten functions of the LMS worked properly according to the criterion set of usability, 2) the quality of the system function evaluated by the subjects of the experiment was at a high level, and 3) the e-lecture could be launched and retrieved in the LMS platform effectively. Keywords: Learning Management System, Electronic lecture, Streaming video, mySQL, PHP Corresponding author: E-mail: kpsirira@kmitl.ac.th